The impact of climate change on food systems, diet quality, nutrition, and health outcomes: A narrative review - Owino, Victor; Kumwenda, Chiza; Ekesa, Beatrice; Parker, Megan E.; Ewoldt, Laina; Roos, Nanna; Lee, Warren T.; Tome, Daniel (Frontiers in Climate, 2022)
Many consequences of climate change undermine the stability of global food systems, decreasing food security and diet quality, and exposing vulnerable populations to multiple forms of malnutrition. The emergence of pandemics such as Covid-19 exacerbate the situation and make interactions even more complex. Climate change impacts food systems at different levels, including changes in soil fertility and crop yield, composition, and bioavailability of nutrients in foods, pest resistance, and risk of malnutrition. Sustainable and resilient food systems, coupled with climate-smart agriculture, are needed to ensure sustainable diets that are adequately diverse, nutritious, and better aligned with contextual ecosystem functions and environmental conservation. Robust tools and indicators are urgently needed to measure the reciprocal food systems-climate change interaction, that is further complicated by pandemics, and how it impacts human health.